PERANCANGAN SISTEM INFORMASI PADA BANK SAMPAH MAJU LANCAR - Purwanto, Arif Budi (Jendela Inovasi Daerah, 2023)
Garbage is one of the important problems in society, because the amount is increasing day by day. The Maju Lancar Garbage Bank was established as a form of Trunan community participation in dealing with waste problems in Magelang. However, administrative management is still carried out manually and conventionally, making it difficult for secretaries to make deposit and transaction reports. This study aims to design a computerized waste management information system that can facilitate the secretary in collecting, processing and storing data and information. The method used in making this information system uses the waterfall method where the design is carried out in a structured manner. The result of this research is a waste management information system that can be applied to the Maju Lancar Garbage Bank. The test results show that the information system can work as needed at the Maju Lancar waste bank. The information system at the Maju Lancar Garbage Bank makes it easier for the secretary to make deposit reports and transactions more quickly and accurately.